Analisis Dampak Adanya Sektor Wisata Alam Arga Hot Spring Terhadap Lingkungan Sekitar Desa Sundakerta Kecamatan Sukahening Kabupaten Tasikmalaya: Ekologi dan Lingkungan - Fakhri, Mohamad; Luthfi Ariel Setiawan; Yasfi Aulia Rafi; Rama Rizkya Rahman Prasyam; Esta Rendra RS (Indonesian Journal of Glasial Geography, 2025)
This study examines the impact of the Arga Hot Spring ecotourism site located in Sundakerta Village, Sukahening District, Tasikmalaya Regency. Arga Hot Spring is known as a natural hot spring destination nestled within a lush pine forest, equipped with various supporting facilities such as camping areas and recreational attractions. The research employs a qualitative approach, with data collected through participatory observation, in-depth interviews with local residents and tourism managers, as well as field documentation. The findings indicate that the presence of Arga Hot Spring has had a positive impact on improving the local economy, raising environmental awareness, and enhancing social participation in tourism development. However, negative effects have also begun to emerge, such as the potential for pollution, traffic congestion, and pressure on the ecosystem if not balanced with sustainable management. Therefore, collaboration between the community, village government, and tourism operators is essential to maintain a balance between economic benefits and environmental conservation.